Organogenesis and Somatic Embryogenesis from Scalps of Musa Spp. Cv. Tanduk - Mohamed Elhorry, Suleiman Mohamed Ahmed (2006)
This study was carried out to establish reliable and efficient regeneration protocols through organogenesis and somatic embryogenesis from scalps of Musa spp. cv. Tanduk. Scalps are highly proliferated meristems which are ideal materials for organogenesis and embryogenesis in Musa spp. Shoot-tips of Musa spp. Cv. Tanduk were cultred on a modified MS (Murashige and Skoog, 1962) medium containing various concentration of 0, 10, 50 and 100 pM BAP with 1.0 pM IAA added to each BAP concentration. The study showed a reasonably high percentage of scalp formation on MS medium supplemented with 100 pM of BAP and 1.0 pM IAA within 16 to 28 weeks after first culture. BAP at 50 pM produced poor quality scalps and 10 pM BAP resulted in higher proliferation of shoot buds. MS without BAP produced only a single elongated shoot from the cultured shoot tips. Subculture was performed on 4 weeks interval. Histological study was done following subculture of the proliferated shoot tip on 100 pM BAP treatment. Continuous changes were observed starting from a dome-shaped apical meristem covered by layers of leaf primordia to a zone of high division activity. This resulted in the proliferation of meristematic clumps aggregated in a cauliflower-like structure (scalps). The scalps appeared as undulating zone with h o w s separating the hdges of naked tiny meristems. Regeneration of shoots fiom scalps was tested on different concentrations of 1 .O, 2.5 and 5.0 pM BAP incorporated into MS basal medium. Treatment with 2.5 pM BAP produced an average of 40.63 shoots, the highest number of shoot-buds after 8 weeks of culture. The highest mean shoot-bud height attained after 8 weeks was 2.19 cm on 1.0 pM BAP. Shoots obtained from scalps were rooted on half strength and full strength MS media and on MS medium supplemented with 1.0, 5.0 and 10 pM IBA. Full-strength MS medium with 5.0 pM IBA produced the highest number of roots per explant (15.08). Meanwhile, the longest root length (1 1.07 cm) was attained in half strength MS medium. However, there was no significant difference root length observed between half-strength MS, full-strength MS and MS with 1.0 pM IBA. Plantlets produced fiom the scalps through organogenesis were acclimatized under 50% shade in four types of growing medium comprising of sand, peat, sand + top soil + goat dung (3:2: 1 vlv) and top soil + sand (1 : 1 v/v). After six weeks, the highest survivability (77.5%) was obtained in medium consisting of top soil + sand + goat dung. This was followed by 67.5 % survivability in both sand and peat media The lowest survivability (65%) was recorded fiom medium containing a mixture of top soil + sand. Plants acclimatised in medium containing top soil + sand + goat dung were observed to be morphologically the best with very green broad leaves and vigorous sterns. Multiplication of shoots from shoot-tip of banana cv. Tanduk was also investigated. The excised shoot-apices were cultured on MS basal medium supplemented with 0, 5, 10, 15 and 20 1M BAP in combination with 1.5 pM IAA in each. It was observed that BAP concentration over subculture cycles affected the mean number of shoots produced from the shoot tips and the mean shoot height (cm) attained. Shoot formation increased with increase in BAP concentrations and vice versa for shoot height. The highest mean number of shoot-buds (17.47) was produced on 20 pM BAP. The mean number of shoot-buds increased with subsequent subcultures at all levels of BAP tested, reaching the highest mean (27.53) at the 20& week of subculture. The highest mean height (2.43 cm) was obtained on MS medium supplemented with the lowest BAP concentration of 5 pM. Meanwhile, the mean shoot-bud height also increased over subculture cycles, reaching 3.14 cm at the fifth subculture (20 weeks). Two pathways of regeneration via somatic embryogenesis, starting fiom the scalps of Musa spp. cv. Tanduk were also investigated. Scalps were excised and cultured in liquid MS medium supplemented with 5.0 and 10 pM 2,4-D. Scalps placed on 10 pM 2,4-D died because of very high incidence of browning and necrosis. Meristematic globules were released fiom the scalps placed in liquid medium with 5.0 pM 2,4-D. The meristematic globules were either rounded, amoeboid or kidney shaped. Following transfer of the meristematic globules to fi-esh medium of the same composition for cell suspension establishment, yellowish embryogenic cells were formed at the periphery of the meristematic globules- The embryogenic cells were released as single cells into the medium which later gave rise to proembryo-like structures. However, these structures failed to regenerate into plantlets. The embryogenic response of scalps was also investigated on half strength MS semisolid medium containing 2.5, 5.0 and 7.5 pM 2,4-D with 1.0 pM zeatin. The study revealed that 5.0 pM 2,4-D with 1.0 pM zeatin produced the highest percentage of (48 %)embryogenic complexes. Histological sections of the embryogenic complexes induced on scalps of Musa spp. C.V. Tanduk revealed the presence of globular structures, pro-embryos and somatic embryos. Two regeneration media, Ganapathi et al. (1999) medium and CBte et al. (1996) medium were tested for plantlet regeneration fiom the embryogenic complexes. Both regeneration media tested did not exhibit high germination percentages which were 14- 17% on Cote et al. (1996) medium and 2-5% on Ganapathi et al. (1999) medium. Embryogenic cell suspensions were initiated from the scalps-derived embryogenic complex, in half strength MS medium supplemented with 5.0 pM 2,4-D and 1.0 pM zeatin. The study revealed that the embryogenic cell suspensions have high potential towards somatic embryogenesis. Homogeneous embryogenic lines were obtained and matured by plating onto filer paper discs wetted with semi-solid MS medium. The somatic embryos produced were placed on modified MS solid medium containing 0.5, 1.0, and 1.5 pM BAP for germination. The highest germination percentage of 52.60% was attained on medium with 0.5 pM BAP. However, there was no significant difference in the percentage of germination between the treatments. Histological observations on the different stages of somatic embryo development showed bipolar somatic embryos, matured somatic embryos with distinct shoots and root meristems, and two apical meristems originating from the same somatic embryo. Scalps were found to be appropriate in vitro materials for organogenesis and somatic embryogenesis. Somatic embryo regeneration through the establishment of embryogenic cell suspensions from the embryogenic complexes was the best for hture researches.